1991
DOI: 10.1093/eurheartj/12.8.924
|View full text |Cite
|
Sign up to set email alerts
|

Acute administration of captopril lowers the natriuretic and diuretic response to a loop diuretic in patients with chronic cardiac failure

Abstract: Angiotensin-converting enzyme inhibitors suppress plasma concentrations of the sodium retaining hormones angiotensin II and aldosterone. This action should potentiate the natriuretic and diuretic effects of loop diuretics. Some studies indicate, however, that the introduction of angiotensin-converting enzyme inhibitors for the treatment of cardiac failure is associated with transient weight gain and the development of oedema. We have compared the natriuretic and diuretic response to intravenous frusemide 40 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…190,252 Clinical experience in patients who are hemodynamically or clinically unstable suggests that the hypotensive effects of ACE inhibition may attenuate the natriuretic response to diuretics and antagonize the pressor response to intravenous vasoconstrictors. 301,302 As a result, in such patients (particularly those who are responding poorly to diuretic drugs), it may be prudent to interrupt treatment with the ACEI temporarily until the clinical status of the patient stabilizes.…”
Section: Hunt Et Al 2009 Accf/aha Heart Failure Guidelines E415mentioning
confidence: 99%
“…190,252 Clinical experience in patients who are hemodynamically or clinically unstable suggests that the hypotensive effects of ACE inhibition may attenuate the natriuretic response to diuretics and antagonize the pressor response to intravenous vasoconstrictors. 301,302 As a result, in such patients (particularly those who are responding poorly to diuretic drugs), it may be prudent to interrupt treatment with the ACEI temporarily until the clinical status of the patient stabilizes.…”
Section: Hunt Et Al 2009 Accf/aha Heart Failure Guidelines E415mentioning
confidence: 99%
“…Conversely, data about the natriuresis in response to furosemide in the absence and presence of inhibitors of the RAS is limited and not consistent. Two studies indicated that the fractional sodium excretion was diminished when the angiotensin-converting enzyme (ACEi) captopril was acutely administered before furosemide in humans with heart failure; however, the captopril dose led to substantial hypotension (48,101). Motwani et al (107) observed that an ultralow dose of captopril (1 mg), which did not decrease MAP in heart failure patients, enhanced the natriuretic actions of furosemide, whereas a higher dose (25 mg) decreased MAP and attenuated the natriuresis.…”
Section: Questions Pertaining To the Natriuretic Response To Furosemidementioning
confidence: 99%
“…Clinical experience in patients who are hemodynamically or clinically unstable suggests that the hypotensive effects of ACE inhibition may attenuate the natriuretic response to diuretics and antagonize the pressor response to intravenous vasoconstrictors (200,201). As a result, in such patients (particularly those who are responding poorly to diuretic drugs), it may be prudent to interrupt treatment with the ACEI temporarily until the clinical status of the patient stabilizes.…”
Section: Practical Use Of Ace Inhibitors Selection Of Patientsmentioning
confidence: 99%